A flexible aerogel thermal insulation building block and preparation method thereof
By treating aerogel and sepiolite, a layer-coated crosslinking structure is formed to prepare flexible aerogel insulation blocks, which solves the problem that self-insulating concrete blocks in the prior art are difficult to meet high strength and low thermal conductivity at the same time, and achieves efficient insulation performance and strength improvement.
Patent Information
- Application Number
- CN202410914285.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-09
AI Technical Summary
While improving the thermal performance of existing self-insulating concrete blocks, it is difficult to meet the performance requirements of high strength and low thermal conductivity at the same time, and the application of aerogels in cement-based building materials is limited.
By treating aerogel and sepiolite, phase change material is introduced into the aerogel pores, modified aerogel is introduced into the sepiolite pores, and layer-coated crosslinking structure is formed by further processing of sepiolite to prepare flexible aerogel insulation blocks.
It significantly improves the insulation performance and strength of concrete blocks, and has simple process and easy-to-get raw materials, making it suitable for large-scale industrial production.
Smart Images

Figure CN118666558B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material preparation, and in particular to a flexible aerogel thermal insulation building block and a preparation method thereof. Background Art
[0002] With the comprehensive advancement and continuous deepening of building energy conservation work, urgent demands have been put forward for different forms of insulation systems, and energy conservation and structural integration have become important directions for the development and application of structural systems. Self-insulating concrete blocks, as the main wall material for energy-saving and structural integration structural systems, have been one of the key development directions in the field of building blocks in my country in recent years. In the prior art, by filling the holes of hollow concrete blocks with foam concrete, its thermal performance can be improved, making it a self-insulating block with integrated structure and insulation, which can meet the energy-saving construction standards of buildings in different regions of my country. However, the internally filled foam concrete insulation material still cannot meet the performance requirements of high strength and low thermal conductivity at the same time.
[0003] Silica aerogel has excellent thermal insulation properties and has been used to develop a variety of building materials such as aerogel felt, boards, coatings, and blocks. However, due to the hydrophilicity and mechanical properties of the interface of silica aerogel itself, its application in cement-based building materials is greatly limited. Among them, the preparation of aerogel cement-based building materials generally adopts simple physical doping, which results in no significant improvement in the thermal performance of the insulation material and a limited doping amount. If a large amount of addition is added, the mechanical properties of the product will be significantly reduced.
[0004] Therefore, providing a new flexible aerogel insulation building block to solve the above-mentioned defects is an urgent problem to be solved. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a flexible aerogel insulation building block and a preparation method thereof. The present invention introduces a phase change material into the aerogel pores and introduces a modified aerogel into the sepiolite pores by processing aerogel and sepiolite, and further processes the sepiolite to modify the modified aerogel inside the sepiolite pores and form a layer-by-layer cross-linked structure. By using the modified sepiolite, the insulation performance and strength of the obtained concrete building block can be greatly improved. The method of the present application has easy-to-obtain raw materials, simple steps, low requirements on process conditions, and can be mass-produced industrially.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a flexible aerogel thermal insulation building block specifically comprises the following steps:
[0008] S1. 80-90 parts by mass of fly ash, 30-40 parts of modified sepiolite, 1-2 parts of carbide slag, 3-4 parts of standard sand, 100-110 parts of water were mixed and stirred for 1-2h to prepare a slurry;
[0009] S2. Add 10-12 parts of quicklime and 1-3 parts of desulfurized gypsum to the stirring slurry in order by mass, and continue stirring for 2-3h, let stand for 1-2h, and remove the supernatant;
[0010] S3. Add 20-30 parts of cement by mass to the slurry treated in step S402, mix and stir for 2-3h, add 4-8 parts of polyvinyl alcohol, 1-2 parts of polyacrylic acid, stir evenly and pour, and let it stand for 3-4h after pouring to thicken it to obtain an insulating mortar;
[0011] S4. Add 5-8 parts of aluminum powder by mass to the insulation mortar, stir well and pour into a mold;
[0012] S5. The insulating mortar in the mold is pre-cured at a temperature of 50-60 ° C for 1-2h, demolded, and cut to obtain the green body of the required size;
[0013] S6. The green body is transferred to an autoclave for high-temperature and high-pressure steam curing to obtain the flexible aerogel insulation building block.
[0014] Preferably, the modified sepiolite is prepared by the following method:
[0015] 40-60 parts of sepiolite by mass are immersed in a 5-8 mol / L HCl solution, stirred for 2-3 hours, taken out, mixed with 15-20 parts of pyromellitic anhydride, stirred for 2-3 hours, added with 20-30 parts of modified aerogel and mixed and stirred for 1-2 hours, then 3-5 parts of sodium nitrate, 1-2 parts of γ-aminopropyltriethoxysilane and 15-20 parts of benzyltetramine are added in sequence and mixed and stirred for 1-2 hours, and then the temperature is raised to 200-250° C. and kept warm for 2-4 hours to obtain the modified sepiolite.
[0016] Preferably, the modified aerogel is prepared by the following method:
[0017] S21. The fly ash is calcined at a temperature of 600-800°C for 3-4h and then removed;
[0018] S22. The calcined fly ash was immersed in a 5-8 mol / L HCl solution, stirred with a magnetic stirrer at 100-120 ° C for 5-8 h, washed with deionized water, filtered, and the filter residue was washed with deionized water until the filter residue was neutral;
[0019] S23. The residue was mixed with a NaOH solution having a concentration of 8-9 mol / L, stirred at 100-120 ° C for 5-6 h, and the reaction solution was vacuum filtered to obtain a filtrate of water glass and a residue of fly ash;
[0020] S24. Add 1-2 mol / L HCl solution to the filtrate of the water glass to adjust the pH value to between 9 and 10, seal and stand for 48-56 hours to generate alcohol gel, and soak in deionized water for 24-72 hours, replacing the deionized water every 24 hours to remove sodium ions;
[0021] S25. The obtained alcohol gel is then placed in an aqueous solution of 20-50% by volume ethanol and aged at 60-80°C for 1 -3d;
[0022] S26. The aged alcohol gel was immersed in a n-hexane-trimethylsilyl chloride solution with a molar ratio of 10-12:1 for 12-16 hours for surface modification and solvent replacement;
[0023] S27. Using a staged heating drying method, the alcohol gel treated in step S26 is dried under normal pressure, and then naturally cooled to room temperature to obtain fly ash-based aerogel;
[0024] S28. Mix 20-30 parts of aerogel and 30-50 parts of liquid paraffin by mass, evacuate to 0-0.5 MPa, maintain the vacuum condition for 12-15 hours, return to normal pressure, and stand for 1-2 hours to obtain modified aerogel.
[0025] Preferably, step S22 can be replaced by: boiling the calcined fly ash in boiling water for 2-3 hours and drying it at 80-100°C.
[0026] Preferably, in step S23, the mass ratio of the NaOH solution to the filter residue is 0.2-0.4:1.
[0027] Preferably, in step S27, the step of stepwise heating and drying is specifically as follows:
[0028] Under normal pressure, the alcohol gel treated in step S106 is heated to 60° C., 90° C., 120° C., and 150° C. in sequence for drying. The drying time under different temperature conditions is 2-3 h.
[0029] Preferably, in step S6, the working parameters of the high-temperature and high-pressure steam curing are defined as follows: temperature of 180-200° C., pressure of 1.2-1.5 MPa, and curing time of 12-15 h.
[0030] Preferably, in step S1, the particle size of the fly ash is 15-20 μm.
[0031] A flexible aerogel thermal insulation building block is prepared according to the preparation method.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention introduces phase change materials into the pores of aerogels and modified aerogels into the pores of sepiolite by treating aerogels and sepiolite, and further treats sepiolite to modify the modified aerogels inside the pores of sepiolite, thereby forming a layer-by-layer cross-linked structure. By using the modified sepiolite, the thermal insulation performance and strength of the obtained concrete blocks can be greatly improved;
[0034] 2. The raw materials of the method of the present application are easy to obtain, the steps are simple, the requirements for process conditions are low, and large-scale industrial production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a process flow chart of the preparation of the flexible aerogel thermal insulation building block of the present invention;
[0036] Figure 2 The present invention is a flow chart of the process for preparing the modified aerogel in the flexible aerogel thermal insulation building block;
[0037] Figure 3 This is a SEM image of the aerogel prepared in steps S21-S27 of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] See also Figure 1-3 , the present invention provides the following technical solutions:
[0040] Example 1
[0041] A method for preparing a flexible aerogel thermal insulation building block:
[0042] S1. 80kg fly ash, 30kg modified sepiolite, 1kg carbide slag, 3kg standard sand and 100kg water were mixed and stirred for 1h to prepare a slurry;
[0043] S2. Add 10kg quicklime and 1kg desulfurized gypsum to the stirring slurry, continue stirring for 2h, let stand for 1h, and remove the supernatant;
[0044] S3. Add 20kg of cement to the slurry treated in step S402 and mix for 2h, add 4kg of polyvinyl alcohol and 1kg of polyacrylic acid, stir evenly and pour, and let it stand for 3h after pouring to thicken it to obtain an insulating mortar;
[0045] S4. Add 5kg aluminum powder to the insulation mortar, stir well and pour into the mold;
[0046] S5. The insulating mortar in the mold is pre-cured at a temperature of 50 ° C for 1h, demolded, and cut to obtain the green body of the required size;
[0047] S6. The green body is transferred to an autoclave and subjected to high-temperature and high-pressure steam curing for 12 hours at 180° C. and 1.2 MPa to obtain the flexible aerogel insulation building block.
[0048] In the above process, the particle size of the fly ash is 15 μm;
[0049] In the above process, the modified sepiolite is prepared by the following steps:
[0050] 40 kg of sepiolite was immersed in a 5 mol / L HCl solution, stirred for 2 hours, taken out, mixed with 15 kg of pyromellitic anhydride, stirred for 2 hours, 20 kg of modified hydrogel was added and mixed and stirred for 1 hour, and then 3 kg of sodium nitrate, 1 kg of γ-aminopropyltriethoxysilane and 15 kg of benzyltetramine were added in sequence and mixed and stirred for 1 hour, and then the temperature was raised to 200° C. and kept warm for 2 hours to obtain the modified sepiolite.
[0051] In the above process, the modified hydrogel is prepared by the following steps:
[0052] S21. The fly ash was calcined at 600 ° C for 3 h and then removed;
[0053] S22. The calcined fly ash was immersed in a 5 mol / L HCl solution, stirred with a magnetic stirrer at 100 ° C for 5 h, washed with deionized water, filtered, and the filter residue was washed with deionized water until the filter residue was neutral;
[0054] S23. The residue was mixed with a NaOH solution having a concentration of 8 mol / L in a mass ratio of 1:0.4, stirred at 100 ° C for 5 h, and the reaction solution was vacuum filtered to obtain a filtrate of water glass and a residue of fly ash;
[0055] S24. Add 1 mol / L HCl solution to the filtrate of the water glass to adjust the pH to 9, seal and stand for 48 h to generate alcohol gel, and soak in deionized water for 24 h;
[0056] S25. The obtained alcohol gel was then placed in a 20% by volume ethanol aqueous solution and aged at 60° C. for 1 d;
[0057] S26. The aged alcohol gel was immersed in a 10:1 molar ratio of n-hexane-trimethylsilyl chloride solution for 12 h for surface modification and solvent replacement;
[0058] S27. Under normal pressure, the alcohol gel treated in step S26 is heated to 60°C, 90°C, 120°C, and 150°C in sequence for drying, and dried for 2 hours under different temperature conditions, and then naturally cooled to room temperature to obtain fly ash-based aerogel;
[0059] S28. Mix 20 kg of aerogel with 30 kg of liquid paraffin, evacuate to 0.1 MPa, maintain the vacuum condition for 12 hours, return to normal pressure, and stand for 1 hour to obtain modified aerogel.
[0060] Example 2
[0061] A method for preparing a flexible aerogel thermal insulation building block:
[0062] S1 90kg fly ash, 40kg modified sepiolite, 2kg carbide slag, 4kg standard sand, 110kg water were mixed and stirred for 2h to prepare a slurry;
[0063] S2. Add 12kg quicklime and 3kg desulfurized gypsum to the stirring slurry, continue stirring for 3h, let stand for 2h, and remove the supernatant;
[0064] S3. Add 30kg of cement to the slurry after step S402 and mix for 3h, add 8kg of polyvinyl alcohol and 2kg of polyacrylic acid, stir evenly and pour, and let it stand for 4h after pouring to thicken it to obtain an insulating mortar;
[0065] S4. Add 8kg aluminum powder to the insulation mortar, stir well and pour into the mold;
[0066] S5. The insulating mortar in the mold is pre-cured at a temperature of 60 ° C for 2h, demolded and cut to obtain the blank of the required size;
[0067] S6. The green body is transferred to an autoclave and subjected to high-temperature and high-pressure steam curing for 15 hours at 200° C. and 1.5 MPa to obtain the flexible aerogel insulation building block.
[0068] In the above process, the particle size of the fly ash is 20 μm;
[0069] In the above process, the modified sepiolite is prepared by the following steps:
[0070] 60 kg of sepiolite was immersed in 8 mol / L HCl solution, stirred for 2 hours, taken out, mixed with 18 kg of pyromellitic anhydride, stirred for 3 hours, 30 kg of modified hydrogel was added and mixed and stirred for 1 hour, and then 5 kg of sodium nitrate, 1 kg of γ-aminopropyltriethoxysilane and 18 kg of benzyltetramine were added in sequence and mixed and stirred for 1 hour, and then the temperature was raised to 250° C. and kept warm for 2 hours to obtain the modified sepiolite.
[0071] In the above process, the modified hydrogel is prepared by the following steps:
[0072] S21. The fly ash was calcined at 800 ° C for 3.5 h and then removed;
[0073] S22. The calcined fly ash was immersed in an 8 mol / L HCl solution, stirred with a magnetic stirrer at 100 ° C for 6 h, washed with deionized water, filtered, and the filter residue was washed with deionized water until the filter residue was neutral;
[0074] S23. The residue was mixed with a NaOH solution having a concentration of 9 mol / L in a mass ratio of 1:0.3, stirred at 120 ° C for 6 h, and the reaction solution was vacuum filtered to obtain a filtrate of water glass and a residue of fly ash;
[0075] S24. Add 2 mol / L HCl solution to the filtrate of the water glass to adjust the pH to 10, seal and stand for 48 h to generate alcohol gel, and soak in deionized water for 24 h;
[0076] S25. The obtained alcohol gel was then placed in a 50% by volume ethanol aqueous solution and aged at 80°C for 3d;
[0077] S26. The aged alcohol gel was immersed in a n-hexane-trimethylsilyl chloride solution with a molar ratio of 11:1 for 15 h for surface modification and solvent replacement;
[0078] S27. Under normal pressure, the alcohol gel treated in step S26 was heated to 60°C, 90°C, 120°C, and 150°C for drying, and dried for 2.5 hours under different temperature conditions, and then naturally cooled to room temperature to obtain fly ash-based aerogel;
[0079] S28. Mix 30 kg of aerogel with 50 kg of liquid paraffin, evacuate to 0.3 MPa, maintain the vacuum condition for 15 hours, return to normal pressure, and let stand for 1 hour to obtain modified aerogel.
[0080] Example 3
[0081] A method for preparing a flexible aerogel thermal insulation building block:
[0082] S1 85kg fly ash, 35kg modified sepiolite, 1kg carbide slag, 4kg standard sand, 105kg water were mixed and stirred for 1.5h to prepare a slurry;
[0083] S2. Add 12kg quicklime and 3kg desulfurized gypsum to the stirring slurry, and continue stirring for 2.5h, let stand for 1h, and remove the supernatant;
[0084] S3. Add 25kg of cement to the slurry after step S402 and mix for 3h, add 6kg of polyvinyl alcohol and 2kg of polyacrylic acid, stir evenly and pour, and let it stand for 4h after pouring to thicken it to obtain an insulating mortar;
[0085] S4. Add 6kg aluminum powder to the insulation mortar, stir well and pour into the mold;
[0086] S5. The insulating mortar in the mold is pre-cured at a temperature of 50 ° C for 2h, demolded and cut to obtain the blank of the required size;
[0087] S6. The green body is transferred to an autoclave and subjected to high temperature and high pressure steam curing for 14 hours at 190° C. and 1.3 MPa to obtain the flexible aerogel insulation building block.
[0088] In the above process, the particle size of the fly ash is 18 μm;
[0089] In the above process, the modified sepiolite is prepared by the following steps:
[0090] 50 kg of sepiolite was immersed in a 6 mol / L HCl solution, stirred for 2 hours, taken out, mixed with 16 kg of pyromellitic anhydride, stirred for 3 hours, 25 kg of modified hydrogel was added and mixed and stirred for 1 hour, and then 5 kg of sodium nitrate, 1 kg of γ-aminopropyltriethoxysilane and 18 kg of benzyltetramine were added in sequence and mixed and stirred for 1 hour, and then the temperature was raised to 250° C. and kept warm for 2 hours to obtain the modified sepiolite.
[0091] In the above process, the modified hydrogel is prepared by the following steps:
[0092] S21. The fly ash was calcined at 800 ° C for 3.5 h and then removed;
[0093] S22. The calcined fly ash was immersed in an 8 mol / L HCl solution, stirred with a magnetic stirrer at 100 ° C for 6 h, washed with deionized water, filtered, and the filter residue was washed with deionized water until the filter residue was neutral;
[0094] S23. The residue was mixed with a NaOH solution having a concentration of 9 mol / L in a mass ratio of 1:0.4, stirred at 120 ° C for 6 h, and the reaction solution was vacuum filtered to obtain a filtrate of water glass and a residue of fly ash;
[0095] S24. Add 2 mol / L HCl solution to the filtrate of the water glass to adjust the pH to 10, seal and stand for 48 h to generate alcohol gel, and soak in deionized water for 24 h;
[0096] S25. The obtained alcohol gel was then placed in a 50% by volume ethanol aqueous solution and aged at 80°C for 3d;
[0097] S26. The aged alcohol gel was immersed in a n-hexane-trimethylsilyl chloride solution with a molar ratio of 11:1 for 15 h for surface modification and solvent replacement;
[0098] S27. Under normal pressure, the alcohol gel treated in step S26 was heated to 60°C, 90°C, 120°C, and 150°C for drying, and dried for 2.5 hours under different temperature conditions, and then naturally cooled to room temperature to obtain fly ash-based aerogel;
[0099] S28. Mix 30 kg of aerogel with 50 kg of liquid paraffin, evacuate to 0.3 MPa, maintain the vacuum condition for 15 hours, return to normal pressure, and let stand for 1 hour to obtain modified aerogel.
[0100] Comparative Example
[0101] Comparative Example 1: There are the following differences between Comparative Example 1 and Example 1. The only difference is that in Comparative Example 1, step S28 originally existing in Example 1 is omitted, thereby canceling the modification treatment of fly ash-based aerogel in Comparative Example 1, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.
[0102] Comparative Example 2: Comparative Example 2 differs from Example 1 in that steps S21-S28 originally existing in Example 1 are omitted in Comparative Example 2, thereby eliminating the preparation of fly ash-based aerogel and its modification treatment, and aerogel is not added during the preparation of the thermal insulation blocks of Comparative Example 2.
[0103] Comparative Example 3: Comparative Example 3 is different from Example 1 in that the preparation step of the modified sepiolite originally present in Example 1 is omitted in Comparative Example 3, thereby eliminating the addition of the modified sepiolite in Comparative Example 3, and only the modified aerogel is added in Comparative Example 3.
[0104] Comparative Example 4: Comparative Example 4 is different from Example 1 in that the aerogel preparation and modification process originally existing in Example 1 is replaced in Comparative Example 4. In Comparative Example 4, the aerogel is prepared by the conventional method of tetraethyl orthosilicate, which is specifically achieved by the following steps:
[0105] Raw materials: tetraethyl orthosilicate (TEOS) 44.6 ml, ethanol 46.6 ml, water 21.6 ml;
[0106] S1. Add 0.1 mol / L HCl, adjust the pH of the solution to 2, and react for 30 min;
[0107] S2. Add 0.1 mol / L ammonia water, adjust the solution pH to 6.2, and gel;
[0108] S3. Add sufficient aging solution TEOS:EtOH = 1:5 (volume ratio), age for one week, pour out the aging solution, and soak in ethanol for two days;
[0109] S4. Pour out the ethanol, add enough modification liquid trimethylchlorosilane TMCS for two days, pour out the modification liquid, and wash with water 5 times;
[0110] S5. Drying at normal pressure: drying at 40°C, 60°C, 80°C, 100°C and 120°C for 2 h respectively to obtain aerogel.
[0111] Performance Test:
[0112] The test results of the performance and thermal conductivity of the thermal insulation blocks described in Examples 1-3 and Comparative Examples 1-4 are as follows:
[0113] Table 1. Test results of thermal insulation block performance and thermal conductivity
[0114]
[0115]
[0116] It can be seen from the product test data of the above embodiments and comparative examples that the thermal insulation blocks prepared in Examples 1-3 have slightly improved mechanical properties, while greatly reduced thermal conductivity and water absorption, compared with the comparative example 4 loaded with ordinary aerogel, so that they have the characteristics of high strength and high thermal insulation performance, and meet the standard requirements of GB / T8239-2014 "Ordinary Concrete Small Building Blocks", which strongly proves that the present invention introduces phase change materials into the aerogel pores and modified aerogels into the sepiolite pores by treating aerogel and sepiolite, and further modifies the modified aerogels inside the sepiolite pores by further treating the sepiolite, thereby forming a layer-by-layer coated cross-linked structure, which greatly improves the thermal insulation performance and strength of the obtained concrete blocks.
[0117] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a flexible aerogel thermal insulation building block, characterized in that: The specific steps include: S1. 80-90 parts by mass of fly ash, 30-40 parts of modified sepiolite, 1-2 parts of carbide slag, 3-4 parts of standard sand, 100-110 parts of water were mixed and stirred for 1-2h to prepare a slurry; S2. Add 10-12 parts of quicklime and 1-3 parts of desulfurized gypsum to the stirring slurry in order by mass, and continue stirring for 2-3h, let stand for 1-2h, and remove the supernatant; S3. Add 20-30 parts of cement to the slurry treated in step S2 by mass, mix and stir for 2-3h, add 4-8 parts of polyvinyl alcohol, 1-2 parts of polyacrylic acid, stir evenly and pour, and let it stand for 3-4h after pouring to thicken it to obtain an insulating mortar; S4. Add 5-8 parts of aluminum powder by mass to the insulation mortar, stir well and pour into a mold; S5. The insulating mortar in the mold is pre-cured at a temperature of 50-60 ° C for 1-2h, demolded, and cut to obtain the green body of the required size; S6. The green body is transferred to an autoclave for high temperature and high pressure steam curing to obtain the flexible aerogel insulation block; The modified sepiolite is prepared by the following method: Immerse 40-60 parts of sepiolite by mass in a 5-8 mol / L HCl solution, stir for 2-3 hours, take out, mix with 15-20 parts of pyromellitic anhydride, stir for 2-3 hours, add 20-30 parts of modified aerogel and mix and stir for 1-2 hours, then add 3-5 parts of sodium nitrate, 1-2 parts of γ-aminopropyltriethoxysilane, and 15-20 parts of benzyltetramine in sequence, mix and stir for 1-2 hours, heat to 200-250° C. and keep warm for 2-4 hours to obtain the modified sepiolite; The modified aerogel is prepared by the following method: S21. The fly ash is calcined at a temperature of 600-800 ° C for 3-4 hours and then removed; S22. The calcined fly ash was immersed in a 5-8 mol / L HCl solution, stirred with a magnetic stirrer at 100-120 ° C for 5-8 h, washed with deionized water, filtered, and the filter residue was washed with deionized water until the filter residue was neutral; S23. The residue was mixed with a NaOH solution having a concentration of 8-9 mol / L, stirred at 100-120 ° C for 5-6 h, and the reaction solution was vacuum filtered to obtain a filtrate of water glass and a residue of fly ash; S24. Add 1-2 mol / L HCl solution to the filtrate of the water glass to adjust the pH value to between 9 and 10, seal and stand for 48-56 hours to generate alcohol gel, and soak in deionized water for 24-72 hours, replacing the deionized water every 24 hours to remove sodium ions; S25. The obtained alcohol gel is then placed in an aqueous solution of 20-50% by volume ethanol and aged at 60-80 ° C for 1-3d; S26. The aged alcohol gel is immersed in a n-hexane-trimethylsilyl chloride solution with a molar ratio of 10-12:1 for 12-16 hours for surface modification and solvent replacement; S27. Using a staged heating drying method, the alcohol gel treated in step S26 is dried under normal pressure, and then naturally cooled to room temperature to obtain fly ash-based aerogel; S28. Mix 20-30 parts of aerogel and 30-50 parts of liquid paraffin by mass, evacuate to 0-0.5 MPa, maintain the vacuum condition for 12-15 hours, return to normal pressure, and stand for 1-2 hours to obtain modified aerogel.
2. The method for preparing a flexible aerogel thermal insulation building block according to claim 1, characterized in that: Step S22 can be replaced by: boiling the calcined fly ash in boiling water for 2-3 hours and drying it at 80-100°C.
3. The method for preparing a flexible aerogel thermal insulation building block according to claim 1, characterized in that: In step S23, the mass ratio of the NaOH solution to the filter residue is 0.2-0.4:
1.
4. The method for preparing a flexible aerogel thermal insulation building block according to claim 1, characterized in that: In step S27, the step of stepwise heating and drying is specifically as follows: Under normal pressure, the alcohol gel treated in step S26 is heated to 60° C., 90° C., 120° C., and 150° C. in sequence for drying. The drying time under different temperature conditions is 2-3 h.
5. The method for preparing a flexible aerogel thermal insulation building block according to claim 1, characterized in that: In step S6, the working parameters of the high-temperature and high-pressure steam curing are defined as follows: temperature of 180-200°C, pressure of 1.2-1.5 MPa, and curing time of 12-15 hours.
6. The method for preparing a flexible aerogel thermal insulation building block according to claim 1, characterized in that: In step S1, the particle size of the fly ash is 15-20 μm.
7. A flexible aerogel insulation building block, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of lightweight thermal insulating wall material of expanded perlite-SiO2 aerogel
CN107759151A